Viver em moradia estudantil: implicações na saúde de seus moradores - Nery Garrido, Edleusa (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
This paper is aimed at identifying the current features of residence halls and their impacts on the residents’ health. Thirty-two students living in such halls were interviewed, and eighty pairs of relationships between the features of the resident halls and their residents’ health were found. Features were labeled as either social or structural. Impacts reported by the residents were categorized as health-related habits, physical features and the residents’ morbidity and emotional, psychological and mental states. It was found that 87.5% of the reported impacts were negative, which was mainly imputed to the structural features, thus pointing out the importance of adopting institutional measures to ensure adequate conditions in those environments in order to prevent and promote the students’ health. Suggested studies on the health of college student that take into account the different institutional environments
Keywords: University students; Students’ health; Higher education